Expanded CD8+CD38+ T Cell Population in Patients With Systemic Lupus Erythematosus Is Linked to Increased Infection Rates: A Prospective Study - Jose Rubio; Morgane Humbel; Lama Mulki; Eri Katsuyama; Suzanne Krishfield; Julianne O'Connell; George C. Tsokos; Vasileios Kyttaris (ACR Open Rheumatology)
Objective One of the leading causes of morbidity and mortality among patients with systemic lupus erythematosus (SLE) is infections. The expression of the ectonucleotidase CD38 on the surface of CD8+ T cells has been linked to compromised cytotoxic function. The aim of this prospective study was to assess whether the presence of CD8+CD38+ in the peripheral blood of patients with SLE can serve as a biomarker for infectious complications. Methods A cohort of 80 patients with SLE were recruited over 18 months. The rate of clinically significant infections and presence of CD8+CD38+ T cells in the peripheral blood were monitored at each clinic visit. The patients were classified into high CD38+ and low CD38+ CD8+ T cells using flow cytometry and a previously established cutoff rate of 28.4%. Results A total of 20 infections were registered over the study period. We observed that the patients with an expanded CD8+CD38+ T cell population in the peripheral blood had a higher rate of recurrent infections and a higher likelihood of infection compared with patients with a low CD8+CD38+ T cell population. The levels of CD38 in CD8+ T cells remained stable over time in the studied subjects. Conclusion High levels of CD8+CD38+ T cells in the peripheral blood of patients with SLE identify a subgroup prone to infections for whom proper clinical measures should be applied.